Police Culture and Change: The Case Of Compstat In Police Organizations - Yusuf Yuksel (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
Organizational change is an important concept in management literature. Most of the studies in this literature refer to the concept of culture due to the multidimensional role it is acknowledged to play in promoting, managing, or impeding planned organizational change efforts. The central purpose of this paper is to understand the change of cultural values in The Newark Police Department a large police department located in the east coast of the USA after the implementation of a popular planned organizational change model known as Compstat. This model has been implemented by numerous police organizations in the United States over the last two decades. The main question is if the introduction of Compstat perceived to have changed the cultural values of the organization? If so, how it changed the cultural values of the Newark Police Department. Data were collected in this case study through in-depth interviews, documents, and observation of the Compstat meetings, and analyzed using grounded theory. The study revealed that technological change i.e., computerization of work , generational differences i.e., education level, new priorities , change of society, leadership, diffusion of new ideas about management, and new policing approaches i.e., community policing, problem oriented policing developed in the academic world have all contributed to the cultural change in the NPD. In addition to these factors, there was an unexceptional agreement regarding the influence of Compstat on the cultural change in the NPD in terms of ‘policing approach’ and ‘management of police organization’. Specifically, officers pointed out the role of Compstat in terms of having a proactive approach in policing that goes along with a ‘can do’ mentality; the centrality of information and crime statistics; the focus on crime analysis instead of reliance on just anecdotal evidence and experience; adaptation of different policing approaches and tactics based on scientific analysis; and a closer relationship with the public. Change in the management in the NPD can be categorized as accountability that goes along with responsibility, organizational flexibility, and institutionalization of performance orientation and follow up mechanisms, and managerial control. However, there was a greater ‘change in philosophy’ than ‘change in practice’, but it was clear that there was substantial movement in the intended directions. The findings suggest designing differently the structure and setting of the Compstat meetings in a way to spur brain storming and promote a learning environment. This paper extends existing works on cultural change by presenting a dynamic and contextual understanding of the change process; presenting the perspectives of not only police managers but also officers from different ranks and positions; and using alternative data sources.